Coastal and Marine Socio-Ecological Systems: A Systematic Review of the Literature - Refulio-Coronado, Sonia; Lacasse, Katherine; Dalton, Tracey; Humphries, Austin; Basu, Suchandra; Uchida, Hirotsugu; Uchida, Emi (Frontiers in Marine Science, 2021)
The socio-ecological systems (SESs) framework provides cross-disciplinary insight into complex environmental problems. Numerous studies have applied the SES framework to coastal and marine environments over the last two decades. We review and analyze 98 of those studies to (i) describe how SES concepts were examined and measured; (ii) describe how the studies included feedbacks and thresholds, and (iii) identify and analyze elements unique to coastal and marine SES frameworks. We find that progress has been made in understanding key SES properties in coastal and marine ecosystems, which include resilience, adaptive capacity, vulnerability, and governance. A variety of methods has been developed and applied to analyze these features qualitatively and quantitatively. We also find that recent studies have incorporated land-based stressors in their analyses of coastal issues related to nutrient runoff, bacterial pollution, and management of anadromous species to represent explicit links in land-to-sea continuums. However, the literature has yet to identify methods and data that can be used to provide causal evidence of non-linearities and thresholds within SES. In addition, our findings suggest that greater alignment and consistency are needed in models with regard to metrics and spatial boundaries between ecological and social systems to take full advantage of the SES framework and improve coastal and marine management.